Breast cancer and neoplasms of the thyroid gland: a bidirectional two-sample Mendelian randomization study - Sun, Yiqi; Wan, Bohan; Liu, Xin; Dong, Jianguo (Frontiers in Oncology, 2024)
BackgroundWith the rising incidence of breast cancer (BC) and neoplasms of the thyroid gland, a potential link between the two has drawn increasing attention. However, the causal relationship remains unclear due to various confounding factors. This study aims to investigate the causality between BC and thyroid tumors using Mendelian Randomization (MR) analysis.MethodsWe conducted a bidirectional two-sample MR analysis, utilizing breast cancer-associated single nucleotide polymorphisms (SNPs) from the Breast Cancer Association Consortium (BCAC) and thyroid tumor-related SNPs from the FinnGen (https://www.finngen.fi/) database. First, we performed univariable MR (UVMR) to assess the causal relationship between BC and both malignant and benign thyroid tumors, followed by reverse causality analysis. To account for potential confounders, we applied multivariable MR (MVMR). The inverse-variance weighted (IVW) method was primarily used, with secondary analyses performed using the weighted median and MR-Egger regression approaches.ResultsUVMR analysis revealed a significant positive causal relationship between BC and malignant thyroid tumors (odds ratio [OR] and 95% confidence interval [CI]: 1.291, 1.143–1.458, P = 3.90×10-5). No causal relationship was found between BC and benign thyroid tumors. The MVMR analysis, adjusting for confounding factors such as smoking, drinking, and body mass index (BMI), confirmed the robustness of the results.ConclusionThis study provides genetic evidence supporting a causal relationship between BC and malignant thyroid tumors. These findings highlight the importance of thyroid cancer screening in BC patients. However, further MR studies or randomized controlled trials (RCTs) are necessary to assess small effects accurately.